Cultural-Based Assessment Instrument for Measuring Junior High School Students’ Mathematical Creativity - Ikhsana, Aulia; Anwar, Lathiful; Sisworo, Sisworo (PRISMA, 2025)
Culture has an important role in facilitating students' mathematical creative thinking skills. The use of cultural context in mathematics learning helps students to understand mathematical concepts in a more relevant and real way. The results of the initial study conducted by the researcher indicated that there are still many students whose mathematical creative thinking skills are still low and teachers still have difficulties in developing appropriate assessments to measure creative thinking skills. This study aims to develop assessment instruments using the Jambi cultural context in measuring the mathematical creative thinking skills of junior high school students that are of high quality (valid, practical, and effective). This development research uses the Plomp development model. The development stages include the initial investigation stage, the development and prototyping stage and the assessment stage. The research subjects were 29 students of class IX.A and mathematics teachers. The results of the study were the quality of the product assessment was valid 3.6 with ‘very valid’ criteria, practical with an average teacher response questionnaire score of 3.25 and an average student response questionnaire score of 2.80 and effective with good differentiating power. The assessment developed is of high quality, namely valid, practical and effective. Thus, this assessment can be used by teachers directly or modified as needed to measure students' creative thinking skills.